Impacts of climate change on infestations of Dubas bug and Batrachedra amydraula on date palms in the middle Euphrates provinces - Al-Jubouri, Hana Saleh Attia; Al-Sabhany, Khamis Daham Muslih (Al-Adab Journal, 2021)
This paper aims to firstly analysis the geographical distributions of palm trees, their productivity and the Dubas bug and Batrachedra amydraula in the middle Euphrates provinces, then detect the values of change in climatic elements. Secondly, demonstrate the linkage between spatial climatic change and insect pests of palms. The paper found that; the climatic conditions, as general averages are optimal suitable for growth of date palms and their production in study area. However, the long-term changes in the climatic elements, especially the temperature and relative humidity, as well as their extremes, contributed to creating an appropriate environment to activity and spread of the Dubas bug and Batrachedra amydraula in the study area. It was also found that the lack of take care in palm trees and not development any government integrated pest controls strategies led to wide spread. That has led to cumulative reduction in the number of palm trees and date production in the middle Euphrates provinces.